Implementation of Content-Based Cosine Similarity Algorithm with TF-IDF and SBERT for Movie Recommendation - Eliata Zefanya Irabela; Norhikmah (Jurnal Sistem Cerdas, 2026)
The number of films continues to increase on streaming platforms often makes users confused in deciding which film to watch. To overcome this research develops content-based movie recommendation system. Representation of the film information obtained through the application of TF-IDF and SBERT to genre and synopsis data. Cosine similarity is used to calculate the closeness between representations. The performance system is then evaluated through the Precision@K, MAP@K, and Recall@K metrics. From the test results, hybrid approach shows better performance more stable than single method. With a MAP value reaching 0.95 Recall 0.95 dan Precission 0.71 . In the future, the development system will still possible by utilizing other types of data, including user interaction data.